The Sumerian Dictionary of the University Museum of the University of Pennsylvania. Edited by Å.W. Sjöberg with the collaboration of H. Behrens, A. Cavigneaux, B.L. Eicher, M.W. Green, E. Leichty, D.M. Loding, St. Tinney. Vol. 1: A. Part II. a2 - abzu2
ersch. 1995